2021
DOI: 10.1002/prp2.703
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of baicalin against pulmonary arterial hypertension vascular remodeling through regulation of TNF‐α signaling pathway

Abstract: Pulmonary arterial hypertension (PAH) is a progressive cardiovascular disease with high mortality. However, there were no efficient medical drugs for PAH to enormously improve the survival and quality of life measures. The present study aimed to explore the protective effect of baicalin against experimental PAH in vivo and vitro. All the experimental rats received intraperitoneal injection of monocrotaline (MCT) to induce PAH model. Baicalin was given by intragastric administration from 2 days after MCT inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Baicalin greatly reduces the expression of NF-κB, TNF-α, IL-6 and IL-1. Baicalin, on the other hand, may reduce pulmonary vascular remodeling by preventing ERK and NF-κB phosphorylation and expression, as well as by suppressing endothelial-to-mesenchymal transition (EndMT) via the BMP/Smad axis and NF-κB signaling ( Zhang et al, 2017a ; Xue et al, 2021 ). By decreasing p-p65 and p-ERK expression and encouraging p-AKT and p-endothelial nitric oxide synthase (eNOS) expression, baicalin ameliorated pulmonary vascular remodeling and cardiorespiratory injury in the development of pulmonary arterial hypertension through the AKT/eNOS, ERK and NF-κB signaling pathways ( Yan et al, 2019 ; Xue et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Baicalin greatly reduces the expression of NF-κB, TNF-α, IL-6 and IL-1. Baicalin, on the other hand, may reduce pulmonary vascular remodeling by preventing ERK and NF-κB phosphorylation and expression, as well as by suppressing endothelial-to-mesenchymal transition (EndMT) via the BMP/Smad axis and NF-κB signaling ( Zhang et al, 2017a ; Xue et al, 2021 ). By decreasing p-p65 and p-ERK expression and encouraging p-AKT and p-endothelial nitric oxide synthase (eNOS) expression, baicalin ameliorated pulmonary vascular remodeling and cardiorespiratory injury in the development of pulmonary arterial hypertension through the AKT/eNOS, ERK and NF-κB signaling pathways ( Yan et al, 2019 ; Xue et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that BA downregulated the mRNA levels of TNF-α, IL-13, IL-6, and ET-1 in pulmonary tissues via blocking the activation of the NF-κB signaling pathway to attenuate PAH. Utilizing the same model, Xue et al (2021) found that BA (20, 50, and 200 mg/kg, i.g. administration) profoundly reduced the mRNA and protein levels of inflammatory factors, excessive proliferation, migration of pulmonary artery smooth muscle cells, and vascular remodeling via the TNF‐α/bone morphogenetic protein receptor 2 (BMPR2) signaling pathway.…”
Section: The Protection Of Ba Against Respiratory Diseasesmentioning
confidence: 98%
“…Studies have shown that baicalin and baicalein can play a role in the treatment of PH in many aspects, such as anti-inflammatory, inhibition of PASMC proliferation and EndMT, reduction of oxidative stress, and stabilization of extracellular matrix [ 66 ]. The improvement of baicalin on PVR may be achieved through the following pathways alone or together, including the regulating tumor necrosis factor-α (TNF-α)/BMPR2 signaling pathway, downregulating p38 mitogen-activated protein kinase (MAPK)/matrix metalloproteinase-9 (MMP-9) signaling pathway, promoting Akt/eNOS, and inhibiting ERK and the NF-κB signaling pathway [ 67 , 68 , 69 ]. Baicalein protects against clinical HPH, in part, through enhanced A2A receptor (A2AR) activity and down-regulation of stromal cell-derived factor-1 (SDF-1)/C-X-C chemokine receptor type 4 (CXCR4)-induced PI3K/Akt signaling [ 70 ].…”
Section: Natural Products For the Treatment Of Phmentioning
confidence: 99%